Equilibrium Currency Crises: Are Multiple Equilibria Self-fulfilling or History Dependent? - Davies, G; Vines, D (CEPR, 1995)
The viability of a fixed exchange rate system is shown to be state-or shock-dependent. We show, simply, Obstfeld's claim that there may be multiple equilibria - multiple shock values for which a regime switch becomes optimal. We distinguish between self-fulfilling and history-dependent crises. In the former, crises may occur due to a jump from one equilibrium to another, even for constant model parameters, including the government's cost of quitting the regime. In the latter, costly expectational adjustment implies that the country's history, embodied in its initial expectations, determines the relevant equilibrium and the likelihood of a crisis.